Generic Access Network(GAN) - Bhatti, Simran; Tayal, Vandana; Gulia, Pooja (IJRDO -Journal of Computer Science Engineering, 2015)
Generic Access Network or GAN is generally an evolving telecommunication system that is used to extend mobile voice, data and multimedia (IMS/SIP) applications over IP networks. Unlicensed Mobile Access or UMA is the commercial name used by mobile carriers for the external IP access into their core networks. More recently, the system has been called the Wi-Fi Calling by a number of handset manufacturers, including Apple and Samsung